Relationship between PAUD (Early Childhood Education) Teacher Professional Competence in the 21st Century toward Early Childhood Students’ Science Ability - Khairiah, Fisna; Eliza, Delfi; Uminar, Ajeng Ninda (Al-Athfaal: Jurnal Ilmiah Pendidikan Anak Usia Dini, 2023)
Professional teachers are teachers who have basic competence within themselves. But most of what happens is still not aware of the importance of competence for teachers. This study aimed to determine the relationship between the professional competence of 21st-century teachers and children's science abilities based on their accreditation. Thus, it can be seen the connection between accreditation and the professional competence of PAUD teachers in children's science abilities. The type of research used in this study is quantitative, using correlational methods. Data collection is done by using a questionnaire. It can be seen that with A accreditation with the achievement of children's natural science abilities for problem-solving abilities with a score of 25%, 28% logical thinking, 22% receiving information, and 25% language skills can see and conclude that the professionalism of teachers in educating children in every learning activity has to keep up with the times. Meanwhile, with schools accredited C, it can be seen that scientific ability is 23%, logical thinking is 29%, information reception is 14%, and language skills are 32%. This can be interpreted as scientific ability with a standard level of achievement in learning activities because educators have not applied it professionally in activities with children. It can be concluded that the competence possessed by a teacher who teaches at a school with different accreditation also has further treatment in the learning process. That way, developing science skills is closely related to teacher professionalism so children can develop their science abilities.